Unplanned Surgery After Transcatheter Closure of Ventricular Septal Defect in Children: Causes and Risk Factors - Yang, Penghui; Wu, Zhijun; Liu, Zhiyuan; Zhang, Jing; Zhou, Hao; Ji, Xiaojuan; Yi, Qijian; Li, Mi (Frontiers in Pediatrics, 2021)
Objectives: To evaluate the causes and risk factors of unplanned surgery after transcatheter closure of ventricular septal defect (VSD) in children. Methods: A total of 773 patients with VSD who had the devices transcatheter released between January 2013 and December 2018 in our institution were retrospectively reviewed. Univariate and multivariate analyses were used to identify the risk factors for unplanned surgery. Results: 24 patients (3.1%) underwent unplanned surgery after transcatheter closure of VSD. The most common cause for unplanned surgery was new-onset or worsening aortic regurgitation (14/24; 58.3%), followed by occluder migration (4/24; 16.7%), complete atrioventricular block (2/24; 8.3%), severe hemolysis (2/24; 8.3%), residual shunt (1/24; 4.2%), and occluder edge near the tricuspid valve chordae (1/24; 4.2%). Logistic regression analysis revealed that primary aortic valve prolapse (OR: 5.507, 95%CI: 1.673-18.123, P=0.005); intracristal VSD (OR: 8.731, 95%CI: 2.274-33.527, P=0.002); eccentric occluder (OR: 4.191, 95%CI: 1.233-14.246, P=0.022); larger occluder size (OR: 1.645, 95%CI: 1.331-2.033, P<0.001); and pulmonary artery systolic pressure ≥45 mmHg (OR: 4.003, 95%CI: 1.073-14.941, P=0.039) were risk factors for unplanned surgery. Conclusions: New-onset or worsening aortic regurgitation was the primary cause for unplanned surgery after transcatheter closure of VSD in children. Primary aortic valve prolapse, intracristal VSD, eccentric occluder, larger occluder size, pulmonary artery systolic pressure ≥45mmHg could increase the risk of unplanned surgery.